Why did socialist economies fail? - Tamás Vonyó; Alexander Klein (University of Kent, School of Economics, 2017)
We present new investment data and revised growth accounts for three socialist economies between 1950 and 1989. Government statistics reported distorted measures for both the rate and trajectory of productivity growth in Czechoslovakia, Hungary, and Poland. Researchers have benefited from revised output data, but continued to use official statistics on capital input, or estimated capital stock from official investment data. Investment levels and rates of capital accumulations were, in fact, much lower than officially claimed and over-reporting worsened over time. Sluggish factor accumulation, declining equipment investment and labor input, contributed much more to the socialist growth failure of the 1980s than previously thought.
Keywords: N14; N64; O47; P27; 330; growth accounting; capital accumulation; Socialism; Eastern Europe